Comparative organelle genomics in Daphniphyllaceae reveal phylogenetic position and organelle structure evolution - Rongxiang Zhang; Ying Liu; Shuwen Liu; Yuemei Zhao; Niyan Xiang; Xiaoman Gao; Tao Yuan (BMC Genomics)
Abstract The family Daphniphyllaceae has a single genus, and no relevant comparative phylogenetic study has been reported on it. To explore the phylogenetic relationships and organelle evolution mechanisms of Daphniphyllaceae species, we sequenced and assembled the chloroplast and mitochondrial genomes of Daphniphyllum macropodum. We also conducted comparative analyses of organelles in Daphniphyllaceae species in terms of genome structure, phylogenetic relationships, divergence times, RNA editing events, and evolutionary rates, etc. Results indicated differences in the evolutionary patterns of the plastome and mitogenome in D. macropodum. The plastome had a more conserved structure but a faster nucleotide substitution rate, and the mitogenome showed a more complex structure while the mitotic genome shows a more complex structure but a slower nucleotide substitution rate. We identified several unidirectional protein-coding gene transfer events from the plastome to the mitogenome based on homology analysis, but no transfer events occurred from the mitogenome to the plastome. Multiple TE fragments existed in organelle genomes, and two organelles showed different preferences for nuclear TE insertion types. The estimation of divergence time indicated that the differentiation of Daphniphyllaceae and Altingiaceae at around 29.86 Mya might be due to the dramatic uplift of Tibetan Plateau during the Oligocene. About 75% of codon changes in organelles were found to be hydrophilic to hydrophobic amino acids. The RNA editing in protein-coding transcripts is the result of amino acid changes to increase their hydrophobicity and conservation in alleles, which may contribute to the formation of functional 3D structures in proteins. This study would enrich genomic resources and provide valuable insights into the structural dynamics and molecular biology of Daphniphyllaceae species.